KEBIJAKAN PENYEDIAAN TEKNOLOGI PASCAPANEN KOPI DAN MASALAH PENGEMBANGANNYA (Forum Penelitian Agro Ekonomi, 2013)
Post-harvest technology plays an important role in increasing value added of agricultural commodities. Postharvest technology makes farming more efficient and increase production through yield loss reduction and improved product quality. Coffee production rapidly develops and it needs support of technology and post-harvest facilities suitable to the farmers that they are able to produce the highest quality coffee beans such as required by Indonesian National Standard (SNI). It will also make the small farmers get profitable farm-gate price. The Indonesian Coffee and Cacao Research Institute and the Research Institute for Agricultural Mechanization  provide the technology from upstream to downstream activities used as the Standard Operating Procedure (SOP) starting from harvesting, sorting, processing, storage, and processing.  Some problems found in coffee post-harvest activities are farmers’ empowerment, technology availability, farmers’ capital, and price incentive.  Technology dissemination is crucial as well as affordable prices of post-harvest machineries to the farmers and partnership between farmers, processors, and exporters.
Keywords: policy; development; post-harvest technology; coffee; kebijakan; pengembangan; teknologi pascapanen; kopi